Age-Related Variation in Sympathetic Nerve Distribution in the Human Spleen - Cleypool, Cindy G. J.; Brinkman, David J.; Mackaaij, Claire; Nikkels, Peter G. J.; Nolte, Martijn A.; Luyer, Misha D.; de Jonge, Wouter J.; Bleys, Ronald L. A. W. (Frontiers in Neuroscience, 2021)
The cholinergic anti-inflammatory pathway (CAIP) has been proposed as an efferent neural pathway dampening the systemic inflammatory response via the spleen. The CAIP activates the splenic neural plexus and a subsequent series of intrasplenic events, which at least require a close association between sympathetic nerves and T cells. Knowledge on this pathway has mostly been derived from rodent studies and only scarce information is available on the innervation of the human spleen. This study aimed to investigate the sympathetic innervation of different structures of the human spleen, the topographical association of nerves with T cells and age-related variations in nerve distribution. Spleen samples were retrieved from a diagnostic archive and were allocated to three age groups; neonates, 10-25 and 25-70 years of age. Sympathetic nerves and T cells were identified by immunohistochemistry for tyrosine hydroxylase (TH) and the membrane marker CD3, respectively. The overall amount of sympathetic nerves and T cells were semi-automatically quantified and expressed as total area percentage. A predefined scoring system was used to analyse the distribution of nerves within different splenic structures. Sympathetic nerves were observed in all spleens and their number appeared to slightly increase from birth to adulthood and to decrease afterwards. Irrespective to age, more than halve of the periarteriolar lymphatic sheaths (PALSs) contained sympathetic nerves in close association with T cells. Furthermore, discrete sympathetic nerves were observed in the capsule, trabeculae and red pulp and comparable to the total amount of sympathetic nerves, showed a tendency to decrease with age. No correlation was found between the number of Tcells and sympathetic nerves. The presence of discrete sympathetic nerves in the splenic parenchyma, capsule and trabecular of human spleens could suggest a role in functions other than vasoregulation. In the PALS, sympathetic nerves were observed to be in proximity to Tcells and is suggestive for the existence of the CAIP in humans. Since sympathetic nerve distribution shows interspecies and age-related variation, and our general understanding of the relative and spatial contribution of splenic innervation in immune regulation is incomplete, it remains difficult to estimate the anti-inflammatory potential of targeting splenic nerves in patients.